Praktik Waris Adat Tunggu Tubang pada Masyarakat Semendo Pajar Bulan Lampung Barat - Rohmansyah; Zayad Abd. Rahman; Abdul Wahab Ahmad Khalil (Institut Agama Islam Negeri (IAIN) Kediri, 2022)
Customary inheritance law in Indonesia has diversity based on regional customs, one of which is waiting for Tubang with a female mayoral inheritance system as the sole heir to receive an inheritance. This paper seeks to understand the system and analysis of Islamic law on the practice of customary inheritance in the village of Pajar Bulan-West Lampung. This type of research is qualitative-empirical and uses the theory of 'urf as an analytical knife. This study found that the practice of inheritance the costom waiting for Tubang in the Semendo community in Pajar Bulan village is carried out in three systems: First, the female mayoral system (the eldest daughter), that is, those who are entitled to receive the inheritance in full and not divided. Second, the male mayorate system which replaces the female mayorate as a waiting Tubang through family deliberations. Third, the ngangkit marriage system, namely the marriage of sons from families who do not have daughters waiting for Tubang to women from relatives who are found waiting for Tubang. Meanwhile, the practice of customary inheritance, waiting for Tubang, is analyzed from sources of Islamic law ('urf). So it can be grouped into three categories: first in terms of form, the customary inheritance of waiting for Tubang is included in the category of customary customs in deeds (al-'urf al-'amaliyah). Both in terms of value, the practice of inheritance waiting for tubang is included in the customary category which is in line with shari'ah principles (al-'urf al-shahih). Thirdly, in terms of scope, the practice of customary inheritance of waiting for Tubang is included in the category of general customs (al'urf al-'am) which applies to the Semendo community of Pajar Bulan Village.